Optimasi Sudut Elektroda dan Kuat Arus Terhadap Kekuatan Tarik Pada Baja ST37 - Usman, Mualifi; Fakhrurozi, Muhammad; Kadaryono, Kadaryono (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2024)
Welding technology is an important process in the field of manufacturing in metal welding. SMAW welding uses electrical energy as a heat source and additional electrodes in joining metal welding. The angle of the electrode and the current strength greatly affect the welding strength. In this research, the design and analysis of variations in electrode angle and current strength in SMAW welding were carried out on tensile strength. The material used for testing is ST37 steel. The electrode angles used are 65o, 70o and 75o. The magnitude of the current used is 3 variations, namely 90 A, 95 A, and 100 A. In this research, the data processing method used is a factorial design with data from the results of tensile strength testing. In this study, the largest tensile strength test results were obtained at an electrode angle of 70o with a current strength of 100 A, getting a result of 32.668 kg/mm2, while the smallest result was obtained at an electrode angle of 65o with a current strength of 90 A, getting a result of 19.96 kg/mm2. The results of this research will be used as a reference for further research with variations in angle and current, using different test materials.